2011
DOI: 10.1016/j.cpr.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance as transdiagnostic: Consideration of neurobiological mechanisms

Abstract: Sleep disturbance is increasingly recognized as an important, but understudied, mechanism in the complex and multi-factorial causation of the symptoms and functional disability associated with psychiatric disorders. This review proposes that it is biologically plausible for sleep disturbance to be mechanistically transdiagnostic. More specifically, we propose that sleep disturbance is aetiologically linked to various forms of psychopathology through: its reciprocal relationship with emotion regulation and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
314
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 481 publications
(353 citation statements)
references
References 163 publications
19
314
0
3
Order By: Relevance
“…33 The similar profile of sleep difficulties across diagnoses supports the use of a transdiagnostic intervention approach. 8,34 A transdiagnostic approach also allows for the addition of optional modules to target any possible disorder-specific presentations. This study also highlights the importance of simply asking service users to subjectively report sleep satisfaction, particularly if being referred on for intervention.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…33 The similar profile of sleep difficulties across diagnoses supports the use of a transdiagnostic intervention approach. 8,34 A transdiagnostic approach also allows for the addition of optional modules to target any possible disorder-specific presentations. This study also highlights the importance of simply asking service users to subjectively report sleep satisfaction, particularly if being referred on for intervention.…”
Section: Implications For Practicementioning
confidence: 99%
“…7 Comorbid sleep diffi culties negatively affect quality of life and functioning, and have been associated with the causation and maintenance of a range of psychiatric disorders, with increased risk of relapse. 2,8 A "cyclical" relationship has been conceptualized, whereby sleep problems exacerbate psychiatric diffi culties and vice versa. Individuals' experience of sleep is subjective, 9 and the literature demonstrates a discrepancy between sleep satisfaction indicators when using validated self-report questionnaires and simply asking users of mental health services, with service users reporting lower rates of diffi culties than empirical measures.…”
mentioning
confidence: 99%
“…These include the hyper arousal model which was reviewed by Reimann et al [4] who reported that primary insomnia may be conceptualized as the final common pathway resulting from the interplay between a genetic vulnerability for an imbalance between arousing and sleep-inducing brain activity, psychosocial/medical stressors and perpetuating mechanisms; and also the transdiagnostic theory which proposes that sleep disturbance is aetiologically linked to various forms of psychopathology through its reciprocal relationship with emotion regulation and its shared/interacting neurobiological substrates in genetics and dopaminergic and serotonergic function [5].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep and mental health are intimately related (Harvey, Murray, Chandler, & Soehner, 2011). In particular, there is robust evidence that sleep complaints are highly prevalent among anxious youth (McMakin & Alfano, 2015;Willis & Gregory, 2015).…”
mentioning
confidence: 99%